Psychological Assessment in Patients With Head and Neck Tumors - Aziz, Sana; Pervaiz, Ayesha; Siddiqui, Fatima; Iqbal, Shaista; Jawed, Aqsa; Maqbool, Shahzad (Biological and Clinical Sciences Research Journal, 2025)
Patients with head and neck tumors frequently experience significant psychological distress due to functional impairment, disfigurement, and the complex nature of treatment. Timely identification of anxiety, depression, and quality-of-life issues is essential for holistic cancer care. Objective: To assess the prevalence and severity of anxiety, depression, and quality-of-life impairments in patients diagnosed with head and neck tumors. Methods: This cross-sectional study included 384 patients with histologically confirmed head and neck tumors. Psychological status was assessed using the Hospital Anxiety and Depression Scale (HADS) and the Patient Health Questionnaire-9 (PHQ-9). Functional and symptom-specific quality of life was evaluated using the EORTC QLQ-H&N35 module. Data were analyzed to determine the prevalence and severity of psychological distress and domain-specific impairments. Results: Among 384 participants, 68.0% were male and the majority were aged between 46–60 years. The most common tumor site was the oral cavity (33.9%), and over half (54.4%) received combined modality therapy. According to HADS, 49.2% of patients had clinical anxiety, while 58.3% showed clinical depression. PHQ-9 results indicated that 36.7% had moderate and 17.2% had severe depression. High mean scores in EORTC domains were observed in dry mouth (71.6), social eating (67.4), and pain (65.2), indicating substantial symptom burden. Conclusion: A significant proportion of patients with head and neck tumors experience clinical levels of anxiety and depression along with considerable functional and social impairments. These findings emphasize the importance of routine psychological assessment and multidisciplinary supportive interventions as part of comprehensive oncological care.